Consistency and Variability of DNA Methylation in Women During Puberty, Young Adulthood, and Pregnancy. (27th July 2017) - Chen, Su; Mukherjee, Nandini; Janjanam, Vimala Devi; Arshad, S Hasan; Kurukulaaratchy, Ramesh J; Holloway, John W; Zhang, Hongmei; Karmaus, Wilfried
Prior DNA methylation (DNA-m) analyses have identified cytosine-phosphate-guanine (CpG) sites, which show either a significant change or consistency during lifetime. However, the proportion of CpGs that are neither significantly different nor consistent over time (indifferent CpGs) is unknown. We investigated the methylation dynamics, both longitudinal changes and consistency, in women from preadolescence to late pregnancy using DNA-m of peripheral blood cells. Consistency of cell type–adjusted DNA-m between paired individuals was assessed by regressing CpGs of subsequent age on the prior, stability by intraclass correlation coefficients (>0.5), and changes by linear mixed models. In the first 2 transitions (10-18 years and 18 years to early pregnancy), 19.5% and 20.9% CpGs were consistent, but only 0.35% in the third transition (from early to late pregnancy). Significant changes in methylation were found in 0.7%, 5.6%, and 0% CpGs, respectively. Functional enrichment analyses of genes with significant changes in DNA-m in early pregnancy (5.6%) showed that the maternal DNA-m seems to reflect signaling pathways between the uterus and the trophoblast. The transition from early to late pregnancy showed low consistency/stability and no changes, suggesting the presence of a large proportion of indifferent CpGs in late pregnancy.